Kashmir issue in a nutshell ; Indian commitments on Kashmir ; The Kashmir dispute : solution through plebiscite : how and why?“ ; The Kashmir dispute : the facts. ([y.y.] Muzafferabad)
4 kitap, 1 ciltte (6 s. ; 8 s. ; 8 s. ; 12 s.)